Outcome of laparoscopic versus open hepatectomy for colorectal liver metastases. Issue 11 (4th October 2012) - Cheung, Tan To; Poon, Ronnie T. P.; Yuen, Wai Key; Chok, Kenneth S. H.; Tsang, Simon H. Y.; Yau, Thomas; Chan, See Ching; Lo, Chung Mau
Abstract: Background: Liver resection provides one of the best oncological outcomes for liver metastases in patients with colorectal cancer. However, long‐term results concerning laparoscopic resection versus open hepatectomy for stage IV colon cancer are still limited. The aim of this study is to compare the survival outcome of laparoscopic liver resection with open liver resection for colorectal metastases. Method: Between October 2002 and September 2011, a total of 1697 patients underwent liver resection for liver tumour and 60 patients underwent pure laparoscopic liver resection. Twenty patients had laparoscopic resection for colorectal liver metastases. Case‐matched control patients who received open liver resection were included for comparison. The immediate operative outcomes and survival outcomes including operation morbidity were compared. Results: Twenty patients underwent laparoscopic resection of liver metastases. Forty patients who had open hepatectomy for colorectal metastases were selected as case control. Comparing the laparoscopic group with the open resection group, the median operating time was 180 min versus 210 min P = 0.059, the median blood loss was 200 versus 310 mL ( P = 0.043). Hospital stay was 4.5 versus 7 days ( P = 0.021), disease‐free survival was 9.8 versus 10.9 months ( P = 0.299), and the median survival was 69.4 versus 42.1 months ( P = 0.235). Conclusions: Laparoscopic liver resection is a safe and effective treatment for liver metastases in patients with colorectal cancer. It is associated with less blood loss and shorter hospital stay when compared with open surgery. Long‐term survival is comparable to the conventional open approach.